Feeding responses by Scolytus scolytus to twig bark extracts from elms - Pajares, J.A.=700 1 Garcia, S.; Diez, J.J.; Martin, D.; Garcia-Vallejo, M.C.
(Es, En)
ilus., 14 ref.
Keywords: SCOLYTUS SCOLYTUS; ALIMENTACION; ULMUS; EXTRACTOS; FLOEMA; ESPAÑA